Determinants of Investment In Islamic Crowdfunding - Ryandono, Muhammad Nafik Hadi; Wijayanti, Ida; Kusuma, Kumara Adji (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
Investment decisions in Islamic Crowdfunding have many determinants, including: project quality, creator abilities, social network creators, reputation and entrepreneur experiences. This study examines the influence of significant and insignificant determinants of investment in Islamic Crowdfunding. It uses a random sampling technique with Structural Equation Modeling Partial Least Square (PLS) as the analysis model. The results show that social creators and entrepreneur experiences have a significant effect on investment in Islamic Crowdfunding. Contrastingly, project quality, creator ability, and reputation have insignificant influences. Entrepreneur experiences and reputation of the platform have dominant and least influence on investment in Islamic crowdfunding, respectively. Creator’s ability has a dominant-negative effect on Islamic Crowdfunding, and therefore, it requires special attention. The sharia values contained in all investment determinants are the primary consideration by investors. Therefore, increasingly inevitable sharia compliance is a necessity from time to time.